2008
DOI: 10.4161/epi.3.5.6755
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive functional assay reveals frequent loss of genomic imprinting in human placenta

Abstract: Loss of imprinting (LOI)is the gain of expression from the silent allele of an imprinted gene normally expressed from only one parental copy. LOI has been associated with neurodevelopmental disorders and reproductive abnormalities. The mechanisms of imprinting are varied, with DNA methylation representing only one. We have developed a functional transcriptional assay for LOI that is not limited to a single mechanism of imprinting. The method employs allele-specific PCR analysis of RT-PCR products containing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 26 publications
4
47
2
5
Order By: Relevance
“…In the previous report, we concluded that LOI is a common phenomenon in the human placenta based on our LOI measurements of nine genes in 27 placentas. 9 In this report we expanded our investigation. We first examined the imprinting status of 27 out of 52 placentally expressed genes.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…In the previous report, we concluded that LOI is a common phenomenon in the human placenta based on our LOI measurements of nine genes in 27 placentas. 9 In this report we expanded our investigation. We first examined the imprinting status of 27 out of 52 placentally expressed genes.…”
mentioning
confidence: 88%
“…We based this list on information from two sources: (1) 61 experimentally determined imprinted genes listed in two databases, i.e., www.geneimprint.com and http://igc.otago.ac.nz/home.html; and (2) 27 imprinted genes identified by Maynard et al using the ChIP-SNP method. 18 While two genes overlapped between the two sources, we excluded an additional 12 genes that: (1) were shown to be imprinted in other human tissues but not in placenta; 8,9 (2) their sequences could not be found in the NCBI and Ensembl databases (www.ncbi.nlm.nih. gov/sites/entrez; www.ensembl.org); and (3) were not large enough to allow primer design.…”
Section: Expression Of Imprinted Genes In Normal and Iugr Placentasmentioning
confidence: 99%
See 3 more Smart Citations